Effect of systematic psychological preparation using visual illustration prior to gastrointestinal endoscopy on the anxiety of both pediatric patients and parents - Pornthawee Riddhiputra (2018)
Background: Anxiety, a psychological response to stress, can affect a child undergoing medical procedures, and their family members. The purpose of the present study was to evaluate the benefit of detailed systematic information using a set of real photograph-based technical illustrations provided to both parents and patients before performing endoscopy on the level of anxiety. Material and Method: All children eligible for gastrointestinal endoscopy were consecutively enrolled from December 2003 to May 2004. Before and after providing systematic psychological preparation, the parents and patients older than five years of age were asked to score their anxiety on the procedures using visual analogue scale (VAS). Results: There were fifty-four patients enrolled during the study period. Of these, twenty-five children were older than five years of age. The most common indication of gastrointestinal endoscopy was lower gastrointestinal bleeding. The esophagogastroduodenoscopy, colonoscopy, and both upper and lower endoscopies were performed in 50%, 37%, and 13% of the cases, respectively. The mean and standard deviation of VAS on anxiety of the parents (n = 54) before and after providing systematic information were 3.89 +/- 3.45 and 1.90 +/- 2.46, respectively (p < 0.001). These values on anxiety of the children older than 5 years of age before and after providing systematic information were 4.38 +/- 3.72 and 3.36 +/- 3.69, respectively (p = 0.143). There was no statistically significant impact of types of procedure, level of education, family's income, age of children, and birth order on the level of anxiety. Conclusion: The preparatory intervention using systematic visual illustration of the technical procedures in children undergoing gastrointestinal endoscopy could significantly reduce the parents' anxiety.